Risk factors of uprising of intranatal injury in newborns - Shkatula, Yuriy; Loboda, Andrey; Aschaulova, Galina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Intranatal injury in newborn is pathological condition developing during childbirth which is characterized by damages to the tissues and organs of the child and is accompanied by disorder of their functions. Over the past decade there was decreasing rate of birth trauma as the cause of death of children in full-term at 2.6 times due to the growth rate of abdominal delivery. Birth injuries in newborns may have serious impact to further physical health and intellectual evolution of a child. Methods: for the study of intranatal damages and for identifing risk factors of their uprising we performed retrospective analysis of 55 cases of intranatal injury. The comparison group consisted of 90 cases when healthy, full-term babies were born. Results: It was found that the birth trauma is the criterion of quality of hospital obstetric care. Direct causes of birth trauma often are often happen after wrong obstetric care and other traumatic methods of delivery. Factors contributing to the occurrence of intranatal injury are associated pathology in patients, duration of the act of birth, gestational age. Nosological structure of intranatal injury generally comparable with the data of the Ukrainian and European registries. Results obtained suggest that there is hyperdiagnostics of intranatal cervical spine injuries. This is due to the lack or unavailability of information content available in the arsenal of traditional methods of instrumental studies, anatomic immaturity of the structures of the cervical spine, fear and reluctance to recognize obstetric trauma. Conclusion: prevention of intranatal damages should be based on the diagnostics of subclinical disorders in pregnant women and their preventive correction; activities aimed at antenatal protection of the fetus, reducing the frequency of miscarriage and rational management of childbirth.